2012
DOI: 10.1186/1745-6215-13-128
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine patches and quitline counseling to help hospitalized smokers stay quit: study protocol for a randomized controlled trial

Abstract: BackgroundHospitalized smokers often quit smoking, voluntarily or involuntarily; most relapse soon after discharge. Extended follow-up counseling can help prevent relapse. However, it is difficult for hospitals to provide follow-up and smokers rarely leave the hospital with quitting aids (for example, nicotine patches). This study aims to test a practical model in which hospitals work with a state cessation quitline. Hospital staff briefly intervene with smokers at bedside and refer them to the quitline. Depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The study protocol was previously reported 25 but a brief overview is provided here. Subjects who provided consent were stratified by recruitment site and cigarettes per day (CPD; six to ten or ≥11) and randomly assigned by computer to one of four groups: usual care, nicotine patches at discharge, proactive quitline counseling, or both.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study protocol was previously reported 25 but a brief overview is provided here. Subjects who provided consent were stratified by recruitment site and cigarettes per day (CPD; six to ten or ≥11) and randomly assigned by computer to one of four groups: usual care, nicotine patches at discharge, proactive quitline counseling, or both.…”
Section: Methodsmentioning
confidence: 99%
“…23,25 Randomization into the nicotine patch condition triggered a flag in the EMR indicating that the patient was to be given a package at discharge that included 8 weeks of patches, with dosing that varied by the number of cigarettes smoked prior to hospitalization. Those who smoked six to ten CPD were provided 6 weeks of 14-mg patches and 2 weeks of 7-mg patches.…”
Section: Methodsmentioning
confidence: 99%
“…Women also received written information at each session. Cognitive behavioral strategies, including preparation for high-risk periods, management of slips, and creation of a relapse plan, successfully have decreased smoking relapse risk in general [41][42][43] and during the postpartum period. 17,20 Therefore, in both interventions women were asked to monitor urges to smoke and discussed strategies to address cravings and high-risk situations.…”
Section: Interventionsmentioning
confidence: 99%
“…Five of the projects were two-arm RCTs comparing active interventions to usual care 6-10 ; one used a factorial design to test the effects of two different interventions alone and in combination 11 ; and the last used group randomization procedures to assign hospitals to intervention and control conditions. 12 Some interventions were initiated during hospitalization, 6,12 but most were delivered post-discharge.…”
Section: Methodsmentioning
confidence: 99%
“…12 Some interventions were initiated during hospitalization, 6,12 but most were delivered post-discharge. 10,11 Table 1 provides study details. 12 …”
Section: Methodsmentioning
confidence: 99%